Suministro de forraje de Arachis pintoi, en la dieta de cuyes de levante y ceba (1996)
In he county of Pitalito (Huila), south of Colombia was a experiment in Cuyes (Cav/apurce/Iu for determinate of respuest to voluntary intake of three levels of Arachisp/nto/forrage with 3.0, 3.5 y 4.0% ; and a group how witness receivers equal alimentation to the others group less Arachis. The results of experiment were analysing through factor design 2x4, the first factor was the sex (two niveles male and female) and the second factor was the four groups with zero, 3.0, 3.5, 4.0% of Arachis pintoi in the diet; in two ages levanter and fattening In the first age was significative diferents among treatment with witness. Among treatment was diferents in the levels of 3.0%, 3.5 y 4.0% though in the two latter levels dont be diferents in the 3.0 and begger levels, is recommendable available the level of 3.5% in animals of levanter.